A Culturally Sensitive Approach to Substance Use Counseling on Campus. Issue 2 (July 2017) - Greene, Catie A.
Abstract : This article presents an integrated approach for counselors providing substance use counseling to college students with sensitivity to the students' gender, culture, development, and readiness and motivation to change. Incorporating the use of relational–cultural therapy and motivational interviewing, the author organizes these complementary modalities along the Transtheoretical Model of behavior change and discusses practical implications for counselors to reduce harm in the context of the college environment. A case illustration is included.